METHODS OF VARIABLE ANALYSIS IN DEMENTIA WHICH IS ASSOCIATED WITH ADULT´S CHRONIC HIDROCEPHALIA - Buil, Sonia; Pelegrina, Manuel; Fernández, Óscar (Anales de Psicología / Annals of Psychology, 1998)
In this investigation we show some methods of analysis about those variables and behaviours which are associated with the HCA. The study was made starting from the clinical revision of 34 patiens(range of 50 - 82 years old). A methodology based on the categoric analysis was applied. The data have been statistically significant for the variables related to the diagnostic and evolution of the physical categories and not for the psychological and neuropsychological ones. These results will be useful to indicatemodels of variables analysis in patients with HCA and also to detect those which are associated to the diagnosis and rehabilitation process.